Incidence and predictors of dehydration among preterm neonates admitted to the neonatal intensive care unit of Southern Ethiopia hospitals: A prospective follow-up study - Mequanint Ayehu Akele; Dires Birhanu Mihretie; Mitsiwa Ruffo; Tamalew Alemie Tegegn; Migbar Sibhat Mekonnen; Abraham Dessie Gessesse; Abel Desalegn Demeke; Kassa Genetu Alem (PLoS ONE, 2025)
Background Dehydration is one of the causes of preterm morbidity and mortality. Many efforts are being implemented to decrease the cause of preterm mortality, but there is a gap regarding dehydration in generating research-supported evidence. Therefore, this study aimed to investigate the incidence and predictors of dehydration among preterm neonates admitted to the neonatal intensive care units of Southern Ethiopia hospitals. Methodology A prospective, institution-based follow-up study was conducted among 363 maternal-preterm neonatal pairs. Data were collected using a checklist and entered into Epidata version 4.4.2.1, and analyzed using STATA version 14. Bi-variable and multivariable regression were computed using the Cox regression model. A statistical significance was declared at a p-value of <0.05 in line with a 95% confidence interval (CI) and hazard ratios. Result This study was conducted among 363 maternal-neonatal pairs. The incidence of dehydration was 41 per 1000 patient-days, with a total of 3546 patient-days observed. Maternal hypertension (AHR) = 2.95, CI: 1.56, 5.58), phototherapy (AHR = 2.71, 95% CI: 1.37, 5.39), nurse to patient ration 1:2 (AHR = 2.62, 95% CI: 1.5, 4.6), kept in incubator (AHR = 3.38, 95% CI: 1.77, 6.45), asphyxia (AHR = 1.58, CI: 1.09–2.30) and absence of every four hour dehydration assessment (AHR = 1.62, CI: 1.42, 3.62) were predictors for incidence of dehydration among neonates admitted in NICU. Conclusion and recommendation In this study, the incidence of dehydration among preterm neonates was high (41 per 1000 patient-days observation). The major associated factors were being under phototherapy, kept in an incubator, maternal hypertension, nurse-to-patient ratio, dehydration assessment practice, and asphyxia. So, establishing strategies on these identified predictor variables could be essential to reduce the suffering of preterm neonates’ dehydration.